2019
DOI: 10.1177/0272989x18823757
|View full text |Cite
|
Sign up to set email alerts
|

Physician and Nonphysician Estimates of Positive Predictive Value in Diagnostic v. Mass Screening Mammography: An Examination of Bayesian Reasoning

Abstract: Background. The same test with the same result has different positive predictive values (PPVs) for people with different pretest probability of disease. Representative thinking theory suggests people are unlikely to realize this because they ignore or underweight prior beliefs when given new information (e.g., test results) or due to confusing test sensitivity (probability of positive test given disease) with PPV (probability of disease given positive test). This research examines whether physicians and MBAs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This variation means that interpretation and usefulness of antibody testing is context specific, an idea that is not intuitive to many. 6…”
Section: The Interpretation Of These Test Results Depends On the Specmentioning
confidence: 99%
“…This variation means that interpretation and usefulness of antibody testing is context specific, an idea that is not intuitive to many. 6…”
Section: The Interpretation Of These Test Results Depends On the Specmentioning
confidence: 99%
“…How would you know it won't affect them?" [38] "You have to be self-con dent in not doing something" [43] Cognitive biases and experiences 12 articles [10,15,[28][29][30][36][37][38][39][40]46,69] "'There might be a bias to a situation where some doctors missed an important nding, when they were a junior doctor, so they always do scans because they are worried that something might happen like years ago" [29] "If you've ever experienced something like that, you can be sure that you'll send patients with vague complaints for further testing much faster. Absolutely" [37] "It's certainly a-hard to be, treating dying people who are young and not to worry about all of this and I, but I try not to change my practice based on my own personal experience of one or two people dying of prostate cancer" [38] "I would say that my clinical experience highly in-uences my ordering
 sometimes I feel a certain way about a patient even though they don't t a certain pro le and I'll end up doing something additional for them" [39] " "Some GPs mentioned their frustration at not being able to offer the patient something useful, at the feeling of empty hands, owing to the lack of a diagnostic or therapeutic plan for patients presenting with unexplained complaints.…”
Section: Results Of Narrative Reviewmentioning
confidence: 99%
“…The second cognitive error is "representative bias" [10,15,48] or "base rate neglect" [10,15,43] which occurs when failing to take into account pre-test probability in estimating post-test probability in the setting of a positive test result. [15,21,43] By overinterpreting positive results, clinicians are more likely to order further tests.…”
Section: Results Of Narrative Reviewmentioning
confidence: 99%
“…[15,21,43] By overinterpreting positive results, clinicians are more likely to order further tests. In Austin's [48] survey, it was found that 10% of physicians had incorrectly deemed positive predictive value to be the same between screening (where pre-test probability is low) and diagnostic (where pre-test probability is high) tests.…”
Section: Results Of Narrative Reviewmentioning
confidence: 99%